NILAI MORAL DALAM NOVEL MEGAT KARYA RIDA K LIAMSI - Yanti, Ulfa Nurazhari; Syafrial, Syafrial; Charlina, Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research, Under the title Moral Value in the Novel Megat by Rida K Liamsi. The purpose of this study is to describe the moral value in the novel Megat by Rida K Liamsi. This type of research is a qualitative descriptive research that seeks to tell the solution of existing problems based on the real data. Data resource is moral value in Megat by Rida K Liamsi. Based on research finding 75 data moral value in novel Megat by Rida K Liamsi. moral Ketuhanan Yang Maha Esa, moral kemanusiaan yang adil dan beradap, moral persatuan Indonesia, moral kerakyatan yang dipimpin oleh hikmat kebijaksanaan dalam permusyawaratan perwakilan, and moral keadilan sosial bagi seluruh rakyat Indonesia. The data about moral Ketuhanan Yang Maha Esa are 27 data, The data about moral kemanusiaan yang adil dan beradap are 14 data. The data about moral persatuan Indonesia are 15. The data about moral kerakyatan yang dipimpin oleh hikmat kebijaksanaan dalam permusyawaratan perwakilan are 14 data, the data about moral keadilan sosial bagi seluruh rakyat Indonesia are 5 data.Keywords : Moral Value, Megat